The care of patients with secondary hypothalamic amenorrhoea. (9th March 2023) - Watson, Chloe
Abstract : Secondary hypothalamic amenorrhoea is a common menstrual disorder affecting women of reproductive age. In some cases, periods become absent due to prolonged stress on the body, caused by undereating, overexercising and psychological stress. Secondary hypothalamic amenorrhoea is often underdiagnosed and undertreated, and patients may be prescribed oral contraception, which can mask the problem. This article will mainly focus on lifestyle factors associated with this condition and its association with disordered eating.